Monte Carlo simulation study of an in vivo four-dimensional tracking system with a diverging collimator for monitoring radiation source (Ir-192) location during brachytherapy: proof of concept and feasibility - Oh, Geon; Lee, Jeongshim; Kim, Hunjung; Kim, Woochul; Kang, Sangwon; Chung, Jinbeom; Jeong, Seonghoon; Lee, Hakjae; Yoon, Myonggeun; Lee, Boram (Frontiers in Physiology, 2024)
Introduction: The aim of this study was to demonstrate the potential of an in vivo four-dimensional (4D) tracking system to accurately localize the radiation source, Iridium-192 (Ir-192) in high-dose rate brachytherapy. Methods: To achieve time-dependent 3D positioning of the Ir-192 source, we devised a 4D tracking system employing multiple compact detectors. During the system’s design phase, we conducted comprehensive optimization and analytical evaluations of the diverging collimator employed for detection purposes. Subsequently, we executed 3D reconstruction and positioning procedures based on the 2D images obtained by six detectors, each equipped with an optimized diverging collimator. All simulations for designing and evaluating the 4D tracking system were performed using the open-source GATE (v9.1) Monte Carlo platform based on the GEANT4 (v10.7) toolkit. In addition, to evaluate the accuracy of the proposed 4D tracking system, we conducted simulations and 3D positioning using a solid phantom and patient data. Finally, the error between the reconstructed position coordinates determined by the tracking system and the original coordinates of the Ir-192 radiation source was analyzed. Results: The parameters for the optimized diverging collimator were a septal thickness of 0.3 mm and a collimator height of 30 mm. A tracking system comprising 6 compact detectors was designed and implemented utilizing this collimator. Analysis of the accuracy of the proposed Ir-192 source tracking system found that the average of the absolute values of the error between the 3D reconstructed and original positions for the simulation with the solid phantom were 0.440 mm for the x coordinate, 0.423 mm for the y coordinate, and 0.764 mm for the z coordinate, and the average Euclidean distance was 1.146 mm. Finally, in a simulation based on data from a patient who underwent brachytherapy, the average Euclidean distance between the original and reconstructed source position was 0.586 mm. Discussion: These results indicated that the newly designed in vivo 4D tracking system for monitoring the Ir-192 source during brachytherapy could determine the 3D position of the radiation source in real time during treatment. We conclude that the proposed positioning system has the potential to make brachytherapy more accurate and reliable.